A Pilot Evaluation of Expedited Partner Treatment and Partner Human Immunodeficiency Virus Self-Testing Among Adolescent Girls and Young Women Diagnosed With Chlamydia trachomatis and Neisseria gonorrhoeae in Kisumu, Kenya. Issue 10 (25th October 2021) - Omollo, Victor; Bukusi, Elizabeth A.; Kidoguchi, Lara; Mogaka, Felix; Odoyo, Josephine B.; Celum, Connie; Morton, Jennifer; Johnson, Rachel; Baeten, Jared M.
Abstract : A pilot study among young women receiving preexposure prophylaxis who were diagnosed with Chlamydia trachomatis or Neisseria gonorrhoeae found high acceptability and uptake of expedited partner treatment and partner human immunology virus self-testing. Abstract : Background: Expedited partner treatment (EPT) is effective for preventing sexually transmitted infection recurrence, but concerns about intimate partner violence and missed opportunities for human immunology virus (HIV) testing have limited its use in African settings. Methods: We conducted a pilot prospective evaluation of EPT among adolescent girls and young women (AGYW) accessing HIV preexposure prophylaxis in an implementation project in Kisumu, Kenya. Those with etiologic diagnosis of Chlamydia trachomatis and Neisseria gonorrhoeae were treated and given the option of delivering sexually transmitted infection medication and HIV self-test kits to their current sexual partner(s). At enrollment, we assessed their reasons for declining. Three months after they delivered medication and kits to the partner(s), we assessed their reasons for failing to deliver medication and kits to their partner and reported partner's reactions. Results: Between September 2018 and March 2020, 63 AGYW were enrolled. The majority (59/63 [94%]) accepted EPT, and 50 (79%) of 63 partner HIV self-testing (HIVST). Three quarters (46/59) of those accepting EPT returned for the assessment visit with 41 (89%) of 46 successfully delivering medication to 54 partners, of whom 49 (91%) used it. Seventy percent (35/50) who took partner HIVST kits returned for the assessment, with 80% (28/35) reporting providing kits to 40 partners, of whom 38 (95%) used it. Reported barriers to EPT and partner HIVST uptake among women who declined included anticipated fear that their partner could become angry or violent and loss of relationship. Conclusions: Both EPT and partner HIVST were acceptable despite noted barriers among Kenyan AGYW with etiologic diagnosis of Chlamydia trachomatis / Neisseria gonorrhoeae and their partners.